A new wine Torulaspora delbrueckii killer strain with broad antifungal activity and its toxin-encoding double-stranded RNA virus - Ramírez, Manuel; Velázquez, Rocío; Maqueda, Matilde; López-Piñeiro, Antonio; Ribas, Juan C. (Frontiers in Microbiology, 2015)
Wine Torulaspora delbrueckii strains producing a new killer toxin (Kbarr-1) were isolated and selected for wine making. They killed all the previously known Saccharomyces cerevisiae killer strains, in addition to other non-Saccharomyces yeasts. The Kbarr-1 phenotype is encoded by a medium-size 1.7 kb dsRNA, TdV-Mbarr-1, which seems to depend on a large-size 4.6 kb dsRNA virus (TdV-LAbarr) for stable maintenance and replication. The TdV-Mbarr-1 dsRNA was sequenced by new generation sequencing techniques. Its genome structure is similar to those of S. cerevisiae killer M dsRNAs, with a 5′-end coding region followed by an internal A-rich sequence and a 3′-end non-coding region. Mbarr-1 RNA positive strand carries cis acting signals at its 5′ and 3′ termini for transcription and replication respectively, similar to those RNAs of yeast killer viruses. The ORF at the 5′ region codes for a putative preprotoxin with an N-terminal secretion signal, potential Kex2p/Kexlp processing sites, and N-glycosylation sites. No relevant sequence identity was found either between the full sequence of Mbarr-1 dsRNA and other yeast M dsRNAs, or between their respective toxin-encoded proteins. However, a relevant identity of TdV-Mbarr-1 RNA regions to the putative replication and packaging signals of most of the M-virus RNAs suggests that they are all evolutionarily related.